STRATEGI PRAKTIK PENDISTRIBUSIAN ZAKAT DI DESA CAMPAKA MASJID NURUL ANFAL: STRATEGI PRAKTIK PENDISTRIBUSIAN ZAKAT DI DESA CAMPAKA MASJID NURUL ANFAL - SAIE, MOH (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2024)
This Study highlights the importance of distributing zakat through the mosque to enhance the community's welfare in Desa Campaka, Kecamatan Pasongsongan, and Kabupaten Sumenep. The research conducted at Masjid Nurul Anfal aimed to understand the strategy of distributing zakat to transform recipients (mustahik) into contributors (muzakki) through the Sejahtera program and identify obstacles in zakat distribution. The study utilised an institutional zakat management approach with a qualitative method, gathering primary data from the research object and secondary data from relevant documents. The findings indicated that the zakat distribution strategy through the Sejahtera program at Masjid Nurul Anfal effectively transformed mustahik into muzakki, significantly benefiting the welfare of the community in Desa Campaka. The research concluded that zakat distribution through the Sejahtera program at Masjid Nurul Anfal plays a crucial role in the transformation of recipients into contributors. To enhance program effectiveness, regular evaluations and improved coordination among stakeholders are recommended.